Is heterogeneity in stage 3 non-small cell lung cancer obscuring the potential benefits of dose-escalated concurrent chemo-radiotherapy in clinical trials?. (April 2018) - Hudson, Andrew; Chan, Clara; Woolf, David; McWilliam, Alan; Hiley, Crispin; O'Connor, James; Bayman, Neil; Blackhall, Fiona; Faivre-Finn, Corinne
Highlights: A review of concurrent chemoradiotherapy in stage 3 non-small cell lung cancer. Recent trial data suggests a detriment to dose-escalated radiotherapy in this setting. Large degree of heterogeneity in patient, tumour and clinical factors between cases. Heterogeneity may be limiting the ability to detect benefits of dose-escalation. Technology advances may better stratify cases and allow safer dose-escalation. Abstract: The current standard of care for the management of inoperable stage 3 non-small cell lung cancer (NSCLC) is concurrent chemoradiotherapy (cCRT) using radiotherapy dose-fractionation and chemotherapy regimens that were established 3 decades ago. In an attempt to improve the chances of long-term control from cCRT, dose-escalation of the radiotherapy dose was assessed in the RTOG 0617 randomised control study comparing the standard 60 Gy in 30 fractions with a high-dose arm receiving 74 Gy in 37 fractions. Following the publication of this trial the thoracic oncology community were surprised to learn that there was worse survival in the dose-escalated arm and that for now the standard of care must remain with the lower dose. In this article we review the RTOG 0617 paper with subsequent analyses and studies to explore why the use of dose-escalated cCRT in stage 3 NSCLC has not shown the benefits that were expected. The overarching theme of this opinion piece is how heterogeneity between stage 3 NSCLC cases in terms of patient, tumour, and clinical factors may obscure the potential benefits of dose-escalation by causing imbalances in the arms of studies such as RTOG 0617. We also examine recent advances in the staging, management, and technological delivery of radiotherapy in NSCLC and how these may be employed to optimise cCRT trials in the future and ensure that any potential benefits of dose-escalation can be detected.